Innovative garbage collector for small worker application / Luqmanul Hakim Jamingan and Radzi Abdul Rasih - Jamingan, Luqmanul Hakim; Abdul Rasih, Radzi (School of Mechanical Engineering, 2023)
Cleaning is an essential necessity for all individuals, requiring regular attention in daily routines. Traditional road and floor cleaning machines are widely employed in various settings, including highways, railway stations, airports, hospitals, bus stops, multi-story buildings, and universities. These machines typically rely on human energy for operation, making them user-friendly and environmentally conscious. This project aims to utilize readily available and cost-effective materials, ensuring ease of manufacturing, use, and regulation. During summer power outages, traditional cleaning devices often suffer from reduced efficiency. To address this issue, a superior alternative in the form of an environmentally friendly, manually operated road and floor cleaner is proposed. Compared to existing machinery, this cleaner demonstrates high efficiency in terms of area coverage, time, and cost of the cleaning process. Additionally, it proves to be a cost-effective solution for implementation